2010
DOI: 10.5194/acp-10-9833-2010
|View full text |Cite
|
Sign up to set email alerts
|

A model study on the influence of overshooting convection on TTL water vapour

Abstract: Abstract. Overshooting deep convection that penetrates into the Tropical Tropopause Layer (TTL) is thought to have an important role in regulating the water vapour content of this region. Yet, the net effect of such convection and the dominant mechanisms remain unclear. This study uses two idealised three-dimensional cloud-resolving model simulations to examine the influence of overshooting convection on water vapour when it penetrates into two different TTL environments, one supersaturated and the other subsa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…In summary, the HIBISCUS and TROCCINOX water vapour and particles measurements were all suggesting moistening of the lower stratosphere by injection of ice crystals by overshooting towers over a convective land region, as observed over Northern Australia Knollenberg et al, 1993;Corti et al, 2008), and Africa (Khaykin et al, 2009), confirmed by the heavier isotopic composition of the water vapour in the stratosphere, characteristic of ice lofted from the troposphere, as observed by Hanisco et al (2007) in situ on the NASA WB-57 aircraft, or remotely by the MIPAS HDO measurements in the stratosphere (Steinwagner et al, 2010). The process, successfully simulated by Grosvenor et al (2007) and Chaboureau et al (2007), is now consistently reproduced by meso-scale non-hydrostatic models (Jensen et al, 2007;Chemel et al, 2009;Hassim et al, 2010).…”
Section: Hydration Of the Lower Stratosphere Over Land Convective Sysmentioning
confidence: 54%
See 2 more Smart Citations
“…In summary, the HIBISCUS and TROCCINOX water vapour and particles measurements were all suggesting moistening of the lower stratosphere by injection of ice crystals by overshooting towers over a convective land region, as observed over Northern Australia Knollenberg et al, 1993;Corti et al, 2008), and Africa (Khaykin et al, 2009), confirmed by the heavier isotopic composition of the water vapour in the stratosphere, characteristic of ice lofted from the troposphere, as observed by Hanisco et al (2007) in situ on the NASA WB-57 aircraft, or remotely by the MIPAS HDO measurements in the stratosphere (Steinwagner et al, 2010). The process, successfully simulated by Grosvenor et al (2007) and Chaboureau et al (2007), is now consistently reproduced by meso-scale non-hydrostatic models (Jensen et al, 2007;Chemel et al, 2009;Hassim et al, 2010).…”
Section: Hydration Of the Lower Stratosphere Over Land Convective Sysmentioning
confidence: 54%
“…The relative contributions of quasi-horizontal and vertical transport to the variation of ozone concentration in the subtropical UTLS around 10 • -20 • S were explored by Borchi et al (2005Borchi et al ( , 2007 faces as a proxy of convection. The first is provided by the MIMOSA contour advection model run every 5 K between 300 K and 700 K initialized by the 6-hourly ECMWF analyses (Hauchecorne et al, 2002), whereas the second is derived from the ECMWF vertical velocity. As shown in Fig.…”
Section: Impact Of Convective Lofting and Meridional Exchange At The mentioning
confidence: 99%
See 1 more Smart Citation
“…Chaboureau et al, 2007;Corti et al, 2008;Chemel et al, 2009;de Reus et al, 2009;Pommereau, 2010), mainly by direct injection of water vapour and ice that sublimates in the stratosphere. However, idealised simulations have shown the importance of prevailing TTL background conditions (Jensen et al, 2007;Hassim and Lane, 2010): by driving the humidity in the TTL towards ice saturation, overshooting convection may dehydrate or hydrate, depending on whether the TTL was supersaturated or subsaturated before. Hassim and Lane (2010) found net hydration in the stratosphere, which was subsaturated, regardless of the TTL humidity.…”
Section: Introductionmentioning
confidence: 99%
“…However, idealised simulations have shown the importance of prevailing TTL background conditions (Jensen et al, 2007;Hassim and Lane, 2010): by driving the humidity in the TTL towards ice saturation, overshooting convection may dehydrate or hydrate, depending on whether the TTL was supersaturated or subsaturated before. Hassim and Lane (2010) found net hydration in the stratosphere, which was subsaturated, regardless of the TTL humidity. At present it is unclear what the relative impacts of these localised storms are on the global scale, though observational campaigns during the early years of this millennium demonstrated a high frequency of overshooting events (Pommereau, 2010), which contrast with the generally assumed scarcity of these events.…”
Section: Introductionmentioning
confidence: 99%